Implementation of E-Tilang in The Gatur Post of Lantas Ledeng in Developing The Legal Awareness of Citizens in Bandung City - Rickie Rizkie Ramadhan; Dede Iswandi (Department of Civic Education, 2020)
Citizens' legal awareness is always the main factor that results in the obedience and obedience of a citizen to the law as a whole. Legal awareness is a key factor in how a person acts and carries out his activities every day. Therefore, legal awareness is important for citizens to have from an early age until they are attached to old age. Citizens as legal subjects are required to obey and obey the law. One form of obedience and obedience to the rules is to use a motorized vehicle by Law No. 22 of 2009 concerning Road Traffic and Transportation. Every motorized vehicle user must obey and obey these rules. If a violation occurs, the police officer must take action against it, with a ticket. E-Tilang is an innovation from the police to make it easier for traffic offenders to pay ticket fines to stop illegal fees and increase legal awareness of citizens to comply with the fines of traffic violations that have been committed.